Hierarchical multi-agent based frequency and voltage control for a microgrid power system. (February 2022) - Vanashi, Hessam Keshtkar; Mohammadi, Farideh Doost; Verma, Vishal; Solanki, Jignesh; Solanki, Sarika Khushalani
Highlights: Proposed method is utilized within various multi-agent configurations. Secondary controller brings frequency and voltage to their nominal value. Agents are software abstractions that utilize ADP to determine control parameters. Online and offline training of model network. Abstract: With the introduction of active devices such as inverters in the microgrid the system stability has been jeopardized. A primary controller fails to maintain the system frequency and hence an additional secondary controller is needed. In this paper, a control technique for an isolated smart microgrid in a multi-agent based infrastructure is studied. The agents are software abstractions that utilize advanced algorithms such as Particle Swarm Optimization (PSO) and Adaptive Dynamic Programming (ADP) to tune the control parameters. The proposed ADP based control approach is applied in different multi-agent structures in the inverter based microgrid which is tested against oscillations in the system. The results show improvement in control performance of the microgrid system using the proposed multi-agent based control method.